Biodiversity and distribution of gastropods at seagrass meadow of Balangdatu waters Tanakeke Island South Sulawesi Indonesia - Magdalena Litaay; Marwa Deviana; Dody Priosambodo (Hasanuddin University, 2017)
The research about the biodiversity of gastropod has been conducted in seagrass meadow of Balangdatu waters, Tanakeke Island, South Sulawesi. The research aims to assess the diversity of gastropod species in Balangdatu waters. Sampling was conducted using quadrate transect method systematically. Three replicates of transect were applied for each station. The result indicates there were 34 species of gastropods from 14 genera and 14 families were found. Diversity index from every station varies from 1,661 to 2, 899. These values range from low to moderate. The diversity, Evenness, and dominance indices showed that Balangdatu waters still in good condition and sustain habitat for gastropod.